EXPORT AND INVESTMENT IN FISHERIES SECTOR IN MALUKU PROVINCE - Manuhutu, Yerimias (Universitas Hayam Wuruk Perbanas, 2011)
Export and investment are considered important parts of the macro variables that affect economicgrowth. The purpose of this study in long-term perspective is to analyze the dynamicbehavior of export and investment and the movement direction of causality between exportsand investment in the province of Maluku. Data used in this research is secondary data, theperiod of 1990-2009. Estimation methods used in this study is Granger Causality Test, VectorAutoregressive (VAR). Results show that based on Granger causality test there is one-waydirection from investment variable to the export of fisheries at lag 1-4, and at lag 5 occurringin two-way relationship between two variables in the model. This proves that investment is avery good instrument to stimulate the expansion of fisheries exports sector towards economicopenness. Dynamic behavior of the movement of exports and investment shows that there arereciprocal relationships between export and investment the results. It provides evidence thatIRF shocks/innovations of the investment variables have a direct impact on exports and viceversa. This means that if export variable decreases, the investment variable also decreases.On the contrary, when export variable increases, the investment variable also increases. Yet,the Cholesky decomposition results show that shocks on fishery exports can be explained eitherby itself or investment. It indicates that variable of investment give better dynamic responsesand more dominant compared to export variable.